What should the inflation target be? Views from 600 economists - Gene Ambrocio; Andrea Ferrero; Esa Jokivuolle; Kim Ristolainen (Bank of Finland, 2022)
In a survey of more than 600 economists, most respondents prefer their central bank to have an explicit inflation target. Roughly half want the central bank to keep its current target. Two thirds of the rest want to raise the target, with a median preferred change of one percentage point. In a hypothetical scenario in which the central bank has no prior history of inflation targeting, an additional 12% of the respondents would prefer a different (typically higher) target than the current one. This result suggests that the costs of changing the current target hold some respondents back from wanting an actual target change. Respondents who are worried about the central bank credibility are less likely to support a target raise. Conversely, preference for a target raise is more likely to come from those who are concerned about the zero lower bound on the nominal interest rate. The average estimate of the equilibrium real interest rate in the sample is 0.6%. However, personal views about the equilibrium real interest rate do not predict a preference for a target raise.
urn:nbn:fi:bof-202205091186
Keywords: C38; E31; E52; E58; 330; expert survey; inflation target; monetary policy